2019
DOI: 10.1001/jamainternmed.2019.0763
|View full text |Cite
|
Sign up to set email alerts
|

Decision Aids for Prostate Cancer Screening Choice

Abstract: Key Points Question What is the association of decision aids vs usual care with shared decision-making in men deciding whether to undergo prostate cancer screening? Findings This systematic review and meta-analysis of 19 randomized clinical trials comparing decision aids for prostate cancer screening (12 781 men) found that decision aids are probably associated with a small reduction in decisional conflict and are possibly associated with an increase in kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 57 publications
4
27
0
3
Order By: Relevance
“…However, improvements in knowledge did not translate into changes in screening preferences. Our finding of increased knowledge is consistent with other DA interventions among general audiences [35,36] and among African American men [28,37,38]. Our finding of an average 13 percentage point increase in prostate cancer knowledge is in line with these previous reports [28].…”
Section: Renderxsupporting
confidence: 92%
See 2 more Smart Citations
“…However, improvements in knowledge did not translate into changes in screening preferences. Our finding of increased knowledge is consistent with other DA interventions among general audiences [35,36] and among African American men [28,37,38]. Our finding of an average 13 percentage point increase in prostate cancer knowledge is in line with these previous reports [28].…”
Section: Renderxsupporting
confidence: 92%
“…We found that men had less decisional conflict after using PCSPrep, which is also consistent with prior DA studies [35,36]. Presumably, improvements in knowledge and clarification of preferences reduces men's ambivalence about decision making and improves decision quality.…”
Section: Renderxsupporting
confidence: 89%
See 1 more Smart Citation
“…The results demonstrate that the majority of prostate cancer decision aids could increase patient knowledge on the subject, but were not specifically geared to facilitate shared decision-making. 114…”
Section: Clinical Ethicsmentioning
confidence: 99%
“…Health-education and screening programs, and culturally appropriate educational outreach and easier access to healthcare are efforts targeted toward AA men, and are needed to address significant healthcare disparities (3). There is consensus in literature since at least 2016 that separate screening guidelines are likely needed for AA men (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%